Legal Aspects of The use of Blockchain Technology in Smart Contracts - Bayu Ajie Sugeng Rahayu; Diana Setiawati (Proceeding International Conference Restructuring and Transforming Law, 2025)
Technology is developing so rapidly that it knows no boundaries. Blockchain smart contracts are one of the real proofs of technological development. This innovation was born out of the urgent need for faster, more convenient, and efficient digital transactions. Its existence is an extension of conventional agreements that have legal validity when the provisions as stated in Article 1243 of the Civil Code are fulfilled. This normatif juridical research is compiled using a statutory approach and the data is obtained from literature studies. Sources of data obtained from primary legal materials in the form of laws and secondary legal materials from literacy that have relevance to the issues raised are then processed with descriptive analysis methods. The objectives are to: 1) Know the legal aspects contained in the use of Blockchain smart contract technology; and 2) Knowing the legal settlement of disputes arising in the use of Blockchain smart contracts. The results of the study indicate that a Blockchain smart contract can be considered a valid agreement if it fulfills the 4 (four) elements of a conventional agreement along with other additional provisions. Its utilization in the cyber world creates friction with international law, so that the implementation, legal protection, and disputes that arise must also pay attention to the provisions of international law. This shows that the Blockchain smart contract is an innovation that provides convenience for the community which also requires more attention, especially its legal status in Indonesia.